Community Media - Fuller, Linda K. author. aut Link
XIII, 258 p. 5 illus.
Keywords: Drawing on case studies, this collection offers international perspectives on how community media serves their audiences. The contributors present perspectives on the ever-burgeoning area of grassroots. Their research represents participant observation, hands-on community involvement, boards of directors, content analysis, and ethical inquiries.